First Line Drug-Resistant Tuberculosis and its Associated Risk Factors in Tertiary Care Hospital of Sudurpaschim Province, Nepal (Far Western Review, 2024)
Tuberculosis (TB) remains a major global health concern, with an estimated 10.8 million cases reported worldwide in 2023. In Nepal, TB poses a persistent public health challenge, particularly due to the increasing resistance to first-line anti-TB drugs, which complicates treatment and raises mortality risk. Limited data from Sudurpaschim Province hinder the implementation of region specific interventions. This study aimed to assess the prevalence of first-line drug-resistant TB (DR-TB) and identify its associated demographic, geographic factors among patients treated at Seti Provincial Hospital in 2023. A retrospective cross-sectional analysis was conducted using records of 653 bacteriologically confirmed TB cases diagnosed between January and December 2023. Drug susceptibility test results, along with demographic and geographic data, were analyzed. The overall prevalence of DR-TB was 9.5%. While no significant gender-based differences were observed, age was a significant risk factor, with the highest resistance found in individuals aged 31–45 years (15.5%) and ≥76 years (11.4%). Dalit patients exhibited the highest resistance rate (14.0%), indicating disparities in healthcare access and adherence. Geographically, municipalities like Tikapur and Bardgoriya showed higher DR-TB prevalence, suggesting localized hotspots. These findings emphasize the need for targeted public health strategies to improve early diagnosis, treatment adherence, and equitable healthcare access, especially among vulnerable populations. The study highlights the importance of localized surveillance and further research to effectively address the burden of drug-resistant TB in Sudurpaschim Province.